Prediction of the incidence of lyme disease using mathematical modeling methods (using the example of the Kirov region) - Elena O. Utenkova; Ilya S. Knyazhev; Nikolay S. Shchur (Журнал микробиологии, эпидемиологии и иммунобиологии, 2025)
Introduction. The Kirov region is an endemic region for Lyme disease (ixodic tick-borne borreliosis), which is caused by climatic conditions, an abundance of ticks and their feeders. The economic damage caused by Lyme disease includes the cost of treating patients and eliminating natural foci. Morbidity forecasting is necessary for planning preventive measures (acaricide treatments, awareness-raising activities with the population) and entomological monitoring. The effectiveness of such measures exceeds the above costs, which underlines the relevance of the study.